2010
DOI: 10.1103/physrevlett.105.135004
|View full text |Cite
|
Sign up to set email alerts
|

Triggered Confinement Enhancement and Pedestal Expansion in High-Confinement-Mode Discharges in the National Spherical Torus Experiment

Abstract: We report observation of a new high performance regime in discharges in the National Spherical Torus Experiment, where the H mode edge "pedestal" temperature doubles and the energy confinement increases by 50%. The spontaneous transition is triggered by a large edge-localized mode, either natural or externally triggered by 3D fields. The transport barrier grows inward from the edge, with a doubling of both the pedestal pressure width and the spatial extent of steep radial electric field shear. The dynamics sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 20 publications
1
49
0
Order By: Relevance
“…Further, such scenarios require H 98 =1.2-1.4 and would be limited to 1.5s duration by NBI ion dump operating limits. H 98 =1.3-1.4 has been obtained transiently in NSTX, but sustaining H 98 =1.15-1.2 is only now beginning to be achieved with Li conditioning [6] in ELM-free conditions in NSTX with a goal of extending this enhanced confinement to small-ELM regimes. With the addition of the 2nd NBI of the Upgrade, Figure 10c shows that higher NBI power (10MW vs. 7.5MW) can reduce the required confinement to H 98 =1.2 for 100% non-inductive scenarios and also enables control of q min with ∆q min = 0.6 by varying the NBI source mix at fixed density.…”
Section: B 2nd Neutral Beam Injectormentioning
confidence: 99%
“…Further, such scenarios require H 98 =1.2-1.4 and would be limited to 1.5s duration by NBI ion dump operating limits. H 98 =1.3-1.4 has been obtained transiently in NSTX, but sustaining H 98 =1.15-1.2 is only now beginning to be achieved with Li conditioning [6] in ELM-free conditions in NSTX with a goal of extending this enhanced confinement to small-ELM regimes. With the addition of the 2nd NBI of the Upgrade, Figure 10c shows that higher NBI power (10MW vs. 7.5MW) can reduce the required confinement to H 98 =1.2 for 100% non-inductive scenarios and also enables control of q min with ∆q min = 0.6 by varying the NBI source mix at fixed density.…”
Section: B 2nd Neutral Beam Injectormentioning
confidence: 99%
“…For ITER, predictive modeling shows that fusion Q scales roughly with square of the pedestal pressure so that to fulfill its mission of high fusion gain (Q = 10), it is essential to achieve an H-mode with sufficiently high pedestal pressure. In NSTX, a very high confinement regime called the enhanced pedestal H-mode with confinement enhanced relative to the predictions of the ITER 1997 H-mode scaling up to H H98y,2 ∼ 1.7 has been observed following lithium application [18]. This level of confinement is sufficient for future ST devices such as a Fusion Nuclear Science Facility (FNSF) [19] or an ST Pilot Plant [20].…”
Section: H-mode Power Thresholdmentioning
confidence: 97%
“…In this section we discuss progress on research on the I-mode [19,[104][105][106][107][108][109], the quiescent H-mode [15,83,[110][111][112][113][114], and the Enhanced Pedestal (EP) H-mode [115][116][117]. Another candidate regime, Enhanced D α (EDA) H-mode [21,118], is discussed briefly in section 6 as studies [ 119] have shown that small ELMs appear in EDA H-mode at sufficiently high β.…”
Section: Naturally Occurring Quiescent Regimesmentioning
confidence: 99%
“…In this scenario, an ELM typically provides a trigger for a confinement bifurcation in which the pedestal T e and T i increase substantially, while the rate of line-average density ramping slows substantially or is arrested. The temporal evolution of a relatively long-lived EP H-mode [116] is shown in figure 30. The ELM trigger preceding the confinement transition is marked with a dashed vertical arrow.…”
Section: Ep H-modementioning
confidence: 99%
See 1 more Smart Citation